The causal role of gut microbiota in susceptibility of Long COVID: a Mendelian randomization study - Li, Zuming; Xia, Qinghua; Feng, Jieni; Chen, Xueru; Wang, Yushi; Ren, Xiaolei; Wu, Siyi; Yang, Rongyuan; Li, Jiqiang; Liu, Yuntao; Lu, Yue; Chen, Jiankun (Frontiers in Microbiology, 2024)
Background: Long COVID is a major challenge facing the public. Gut microbiota is closely related to Long COVID.However, the causal effects between gut microbiota and Long COVID remains unclear.Methods: Using summary statistics from Genome-Wide Association Studies (GWAS), Mendelian Randomization (MR) analyses were performed to investigate the relationship between gut microbiota and Long COVID. The primary statistical method employed was Inverse Variance Weighted (IVW). Sensitivity analyses were then conducted to evaluate the reliability of the findings and account for potential confounding variables. Finally, a reverse MR analysis was conducted to examine potential associations between Long COVID and genetically predicted gut microbiota compositions.: There were 2 positive and 1 negative causal effect between gut microbiota and Long COVID. Meta-analysis results show that genus Parasutterella (OR = 1.145, 95%CI = 1.035 ~ 1.266, P = 0.008) and genus Oscillospira (OR = 1.425, 95%CI = 1.235 ~ 1.645, P < 0.001) significantly increased the risk of Long COVID. And genus Eisenbergiella (OR = 0.861, 95%CI = 0.785 ~ 0.943, P = 0.001) significantly decreased the risk of Long COVID. Neither the pleiotropy nor the heterogeneity was observed. Reverse causal effect does not hold. Conclusions: Our research has provided genetic evidence that establishes multiple causal relationships between the gut microbiota and Long COVID, supporting the role of the gut microbiota in Long COVID. It is possible that different taxa play a role in the development of Long COVID. The causal relationships identified in this study require further investigation.